Analysis of plant life forms in Aktobe region - S. A. Aipeissova (Acta Biologica Sibirica, 2017)
In the article the analysis of life forms from 8 floristic complexes of the Aktobe flora region is given on 30 years of field and literary data. In every complex the life forms were described according to C. Raunkiaer and I. G.  Serebryakov; for a meadow floristic complex we applied the method of L.I. Kazakevich. In the steppe floristic complex of the Aktobe flora region the hemicryptophytes were the dominants and had 52.4% from all the species, the subdominant were therophytes – 26.7% or 122 species. Species distribution according to Serebryakov’s life forms showed obvious predominance of polycarpics that were 60.7% from all the species. The study of life forms of calciphilous floristic complex by Raunkiaer defined obvious predominance of hemicryptophyte compiled about of 54.8% from the total species number. Analysis of petrophilous floristic complex by Serebryakov showed the next pattern: pivot root grass herbares made – 26.4%, short rhizome plants – 10.5%, long rhizome plants – 4.6%, and turf rhizome plants – 4.1%. The analysis of life form of halophilous floristic complex defined the predominance of therophytes (38.2%).